Medical certification of incapacity in guardianship applications: conceptualising capacity. (February 2016) - Russ, Tom C.; Thomson, Alison; Lyons, Donald
Abstract : Aims and method: To examine how capacity is recorded in practice and compare this with the statutory definition, medical reports accompanying a random 10% sample (183 applications; 360 reports) of guardianship applications granted in 2011–2012 were examined. Results: Clinicians did not explicitly use the statutory definition of capacity in 47.5% of reports. Over half of applications (56.4%) did not explicitly link the powers sought with the patient's vulnerabilities; such a link was less common in older adults ( P = 0.0175). Clinical implications: Guardianship orders can justify deprivation of liberty. Therefore it is important that such cases involve a thorough assessment of the person and that due process is followed, including adherence to the statutory definition of capacity. Practice could be improved by altering the paperwork required of medical practitioners, in line with mental health legislation. In addition, these findings should inform current legislation reform.